A Systematic Review of Clinical Practice Guidelines for Acute Procedural Pain on Neonates. Issue 5 (May 2020) - Balice-Bourgois, Colette; Zumstein-Shaha, Maya; Vanoni, Federica; Jaques, Cécile; Newman, Christopher J.; Simonetti, Giacomo D.
Abstract : Objectives: During hospitalization in neonatal intensive care units, neonates are exposed to many painful procedures within a stressful environment. To date, many evidence-based guidelines are available. However, the quality of these guidelines and their clinical application remain unclear. This systematic review aimed to determinie the quality of existing guidelines on the management of procedural pain in neonates and to summarize the recommendations provided by these guidelines. Materials and Methods: A structured search was conducted in Embase, PubMed, CINAHL, JBI database, and gray literature resources in November 2018 to identify relevant guidelines published from 2007 onward. Published guidelines and guidelines from complementary searches were included in the treating assessment or management of procedural pain in neonates. The methodological quality was analyzed using the Appraisal of Guidelines for Research and Evaluation (AGREE) II Instrument. Results: A total of 1154 records were identified. After screening for eligibility, 17 guidelines were included in this review. Among these, 11 were identified to be high-quality guidelines. Besides the usual recommendations for pharmacological and nonpharmacological treatments, the inclusion of parents, improving interprofessional collaboration, and considering the setting were identified as important elements. Discussion: The results of this review show that there is a need to improve the methodological quality of guidelines for procedural pain in newborns. The set of recommendations for procedural pain prevention needs to involve not only pharmacological and nonpharmacological pain treatment but also parents and interprofessional collaboration. It is also essential to take into account facilitators, barriers, and the context to improve pain management. Abstract : Supplemental Digital Content is available in the text.